The Influence of Family Economy, Learning Facilities, and Homeroom Teachers on IPAS Learning Attitude - Nurjannah Nurjannah; Elpisah Elpisah; Muhammad Fahreza W; Suarlin Suarlin (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This quantitative research investigates the influence of Family Economics, Learning Facilities, and Student Guardians on the Science Learning Attitudes of fourth-grade students at SDN Barombong. Using a saturated sampling method, the study involved 85 students from three classes. Data were collected through questionnaires and analyzed using multiple regression, t-tests, and F-tests via SPSS 26. The results show that Family Economics, Learning Facilities, and Student Guardians each have a positive and significant effect on students’ science learning attitudes. Collectively, these variables significantly influence learning attitudes, with Family Economics emerging as the most dominant factor. The findings highlight the critical role of socio-economic and educational support factors in shaping student attitudes toward science learning in primary education.